Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Pengangguran Terbuka Di Provinsi Jawa Timur Pada Tahun 2000-2019 - Devi Fadhilatur Rahmah; Wahyu Hidayat , Riyanto (Jurnal Ilmu Ekonomi JIE, 2021)
This study aims to determine the factors that influence the open unemployment rate in the province of East Java which is measured using multiple linear regression using the SPSS application. The type of data used in this study is secondary data, namely data in the form of time series data including open unemployment, inflation, provincial minimum wages and economic growth. The data in this study were obtained from the Central Statistics Agency for East Java and the Central Indonesian Statistics Agency. The analytical method used in this study uses multiple linear regression analysis with the help of SPSS software. The results of this study indicate that the inflation variable and the rate of economic growth have an effect on the open unemployment variable. Meanwhile, the Provincial Minimum Wage variable has no significant effect on the open unemployment variable.